Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1177/107110078600700105
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Study Using Cadaveric Toes to Test the Stability of Fixation Techniques Employed in Arthrodesis of the First Metatarsophalangeal Joint

Abstract: Arthrodesis of the first metatarsophalangeal joint of 15 pairs of cadaveric big toes were performed. The arthrodesis site was shaped with either a dome and socket or planar surface contact between the metatarsal head and proximal phalanx. A template was used to standardize the position of arthrodesis in 20 degrees of valgus and 20 degrees dorsiflexion. Various fixation devices were used to hold this position in corresponding pairs of specimens, and these fixation devices were tested to determine their relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…In matched cadaver studies, cancellous screws with planar joint excision provided the most stability. 11 Curtis et al 12 showed that conical reaming with a lag screw had the best fixation and had statistically significant greater stiffness. Rongstad et al 13 showed that a dorsal miniplate is stronger when compared with a cancellous screw with a miniplate, a Herbert screw, and a Steinman pin.…”
Section: Discussionmentioning
confidence: 99%
“…In matched cadaver studies, cancellous screws with planar joint excision provided the most stability. 11 Curtis et al 12 showed that conical reaming with a lag screw had the best fixation and had statistically significant greater stiffness. Rongstad et al 13 showed that a dorsal miniplate is stronger when compared with a cancellous screw with a miniplate, a Herbert screw, and a Steinman pin.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of techniques can be used for joint preparation and fixation of the first MTPJ . 24,68,1317 Joint preparation usually involves creation of a congruent cup-and-cone articulation or two flat surfaces. Fixation of the arthrodesis can consist of single or multiple Kirschner wires or Steinman pins, single or multiple lag screws of different sizes, plate and screw fixation alone, or plate and screw fixation augmenting a lag screw.…”
Section: Discussionmentioning
confidence: 99%
“…1–5,7,8,10,11,13,15 There are a variety of techniques of first MTPJ arthrodesis. 25,7,8,11,1317 Most authors agree that the hallux should be positioned in 5 to 10 degrees of valgus and 20 to 25 degrees of first MTPJ extension with neutral rotation. 1,4,5,7,8,10,13,14,16 Preparation of the joint surfaces can be done with flat cuts or with a ball-and-cup configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Fixation methods can include Kirschner wires alone, lag screws alone, plate and screw constructs, or plate and screws augmented with lag screws. 7,19,20,22 Reported fusion rates are typically greater than 85%, but can vary from as little as 40% all the way up to 100%. The ideal fusion technique should be strong, reproducible, and relatively easy to perform.…”
Section: Introductionmentioning
confidence: 99%